The psychology of being an Olympic favorite - Haberl, P. (Athletic Insight - The Online Journal of Sport Psychology, 2007)
Athletes take on various roles at the Olympic Games. The role of being the favorite is particularly challenging for aspiring U.S. Olympians. Preparing effectively for the emotional roller coaster of the Olympics is very important for athletes who compete in the role of the favorite. Cognitive-behavioral interventions and mindfulness are excellent tools for the sport psychology consultant to equip the athletes to optimize their Olympic experience. Within this report, I will consider based on experiences working with American Olympic athletes, what the psychological challenges are of being an Olympic favorite.